Some Considerations on Tunneling Losses in Field-Effect Devices for Low-Voltage Microcontrollers - M. A. Grado-Caffaro; M. Grado-Caffaro (Active and Passive Electronic Components)
The loss power density associated with the tunneling current in a typical MOS cell with a floating gate is evaluated for high electric-field strengths in the oxide layer. Furthermore, problems related to oxide thickness are discussed.